Bioaugmentation for the improvement of nitrification in wastewater treatment - Stephenson, Dianne (Cranfield University, 1993)
The literature relating to nitrification in wastewater treatment and bioaugmentation as a method to enhance wastewater treatment processes is reviewed. The use of a commercially available bioaugmentation product (based on a Nitrosomonas culture), which claimed to enhance nitrification in biological wastewater treatment was investigated.The product was tested in full scale trials, in shake flask experiments and its efficacy modelled using a simple activated sludge simulation. At full scale trickling filter plants a bioaugmentation product designed to enhance BOO removal was also tested. This product increased BOO removal by up to 7% in the recovery period following low temperature. The Nitrosomonas culture improved percentage ammonia removal by nearly 10% in trickling filters even at low temperatures of 6.5°C. A maximum improvement of 20% occurred at one trickling filter site at higher temperatures. At activated sludge sites the Njtrosomonas culture improved the nitrifying ability of the activated sludge, as assessed by the laboratory standard method, and at one site noticeably improved percentage ammonia removal during periods of high dosing. At one site the maximum improvement was an increase of 22% in percentage ammonia removal during high dosing. However the operational parameters, loads, hydraulic retention time, mixed liquor suspended solids, sludge age and temperature had a great effect on nitrification. If better process control was applied at one of the works the plant would have had little trouble nitrifying i.e. lower loads, higher HRT, MLSS and sludge age during low temperatures. Sludge wastage regimes contributed greatly to the failure to nitrify. It was found that the activity of the Nitrosomonas culture increased with temperature and acclimatisation and decreased on inoculation into activated sludge. The product facilitated nitrification when inoculated into non-nitrifying activated sludge. Ammonia removal increased with size of inoculum. The simple dynamic model described showed the development of a Njtrosomonas population from inoculation with the Nitrosomonas culture. The model showed that the effectiveness of a bioaugmentation product in activated sludge would depend on the amount of nitrifiers returned to the aeration basin more than other operational factors. The model predicted full nitrification at one of the full scale sites within three days. Bioaugmentation did enhance nitrification at full scale works. However, dosage rates required for improvement meant that conventional methods such as better process control or retrofitting would be economically more feasible.